Internal Differences In The Use Of Land Resources In The Agriculture Of Kashkadarya Region (Eurasian Journal of History, Geography and Economics, 2023)
The soil, climate and other natural conditions of Kashkadarya region are a favorable region in the republic for the development of agriculture. Based on this, this article analyzes the use of land resources in the regions, regions and rural districts